MOVING FROM PROFESSIONAL ORIENTATION PROGRAMES WITHIN THE EDUCATION SYSTEM, TOWARDS NATIONAL PROFESSIONAL ORIENTATION PROGRAMES - Nazelskis, Eugenijus; Laurinaitis, Arūnas (Acta Paedagogica Vilnensia, 2014)
In Lithuania, where the economy is recovering from the crisis, many industrial enterprises encounter sharper increased shortages of qualified workers. However, in most cases this shortage in the country’s labor market is not around some one particular profession that raises selectively the requirements for human qualifications in knowledge, health, or psychic particularities, but for a multitude of popular vocations, such as for long-distance drivers, welders, cooks, etc.The national labor market frequently encounters paradoxical situations; during times of high unemployment and expanded educational levels employers ask the state for permission to import third country specialists because of deficits in many vocations. For some professions such shortages have already existed for several years with no indications of future improvement.Therefore, in order to balance the specialists’ requirements for the state and the labor market, many tasks arise for professional orientation. However, the situation in the labor market shows that the presently active national program for professional orientation limited within the framework of the educational system is not able to fully secure the country’s requirements for specialists.This prompts the search for the ways and means of improving the situation.The research has revealed that industrial subjects which should be the most interested part in satisfying the demand of specialists in the labour market do not participate in professional orientation at all or participate to a little extent. Iindustrial subjects have no programs of professional orientation and do not finance them. Furthemore, the research showed that the existing distinction between supply and demand in professions is formed not by the human factor of Lithuanian people or their intellectual or physiological ability to learn professions needed in the labour market. It appears because of axiological differences between personel choice and of fering a profession, and employers’ needs and expectations.To change the attitude of industrial subjects towards professional orientation, it is inmportant for enterprises and organizations to understand the advantage the effective professional orientation brings to them. Furthemore, in the process of preparing the management of human resources, it would be reasonable to supplement the programs with the course of professional orientation. Having specialists of professional orientation in enterprises and organizations would help to raise professional orientation in Lithuania to a higher level.
Keywords: professional orientation; labour market demands; professional orientation programme; role of companies in the process of professional orientation